2013
DOI: 10.1016/j.psyneuen.2012.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-five years of research on the behavioural malaise associated with influenza and the common cold

Abstract: Minor illnesses such as the common cold and influenza are frequent and widespread. As well as specific symptoms such as nasal problems and fever, these illnesses are associated with a behavioural malaise. One feature of this malaise is reduced alertness and this has been confirmed using subjective reports and objective measures of performance. Such effects have been obtained with both experimentally induced infections and in studies of naturally occurring illnesses. The mechanisms underlying the effects are un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 71 publications
0
24
0
Order By: Relevance
“…Similarly, Matthews and Davies (1998) noted that energetic arousal appears to be more closely linked to vigilance than is tense arousal; use of the task engagement factor to capture subjective energy may be one of the more effective ways of exploring arousal processes. Parasuraman's (e.g., 2003) later work on neuroergonomics advocated for a more differentiated view of neural bases of attention, an approach that has been productive in understanding the impact of the common cold (Eccles, 2009;Smith, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Matthews and Davies (1998) noted that energetic arousal appears to be more closely linked to vigilance than is tense arousal; use of the task engagement factor to capture subjective energy may be one of the more effective ways of exploring arousal processes. Parasuraman's (e.g., 2003) later work on neuroergonomics advocated for a more differentiated view of neural bases of attention, an approach that has been productive in understanding the impact of the common cold (Eccles, 2009;Smith, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…However, modeling suggested that the effect of cold infection on vigilance was fully mediated by loss of task engagement, implying that infection leads to a depletion of resources that can be indexed by subjective state change. There are several possible neural mechanisms for cold effects (Eccles, 2009;Smith, 2013), including immunological changes (central cytokine production), effects on the trigeminal nerve, and changes in neurotransmitter function, as well as indirect effects of sleep loss. Eccles (2009) further notes that cytokines may alter dopamine and serotonin metabolism in the basal ganglia.…”
Section: Discussionmentioning
confidence: 99%
“…Acute respiratory infection (ARI), including common cold, influenza, and influenza-like-illness, is very common, and leads to substantive morbidity, mortality, and economic harms. Evidence suggests that psychological, social and behavioral factors influence susceptibility to ARI illness [1][2][3][4]. For example, people with higher levels of perceived stress [5][6][7][8], emotional reactivity [9], recent stressful life events [10,11], and negative emotional styles [12,13] are at greater risk for ARI illness.…”
Section: Introductionmentioning
confidence: 99%
“…2, 3 Although these adaptive sickness behaviors are a normal component of the innate immune response, amplified or prolonged neuroinflammation can lead to maladaptive sickness responses, increased absenteeism, and general feeling of discomfort. 4 Notably, previous studies have demonstrated that dietary interventions such as resveratrol and α-tocopherol reduced central inflammation and alleviated sickness behavior in mice treated with LPS. 5, 6 These studies and others suggest that nutritional supplements are useful to mitigate the molecular and behavioral changes that occur during acute infection.…”
Section: Introductionmentioning
confidence: 99%